Village in the dark - Yamashita, Iris (Berkley, 2024)
"Detective Cara Kennedy thought she'd lost her husband and son in an accident, but harrowing evidence has emerged that points to murder-and she will stop at nothing to find the truth in this riveting mystery from the author of City Under One Roof. On a frigid February day, Anchorage Detective Cara Kennedy stands by the graves of her husband and son, watching as their caskets are raised from the earth. It feels sacrilegious, but she has no choice. Aaron and Dylan disappeared on a hike a year ago, their bones eventually found and buried. But shocking clues have emerged that foul play was involved, potentially connecting them to a string of other deaths and disappearances. Somehow tied to the mystery is Mia Upash, who grew up in an isolated village called Unity, a community of women and children in hiding from abusive men. Mia never imagined the trouble she would find herself in when she left home to live in Man's World. Although she remains haunted by the tragedy of what happened to the man and the boy in the woods, she has her own reasons for keeping quiet. Aided by police officer Joe Barkowski and other residents of Point Mettier, Cara's investigation will lead them on a dangerous path that puts their lives and the lives of everyone around them in mortal jeopardy"--